Physiological responses associated with capture and crowding stress in matrinxã Brycon cephalus (Gunther, 1869) - Da Rocha, Rossineide Martins; Carvalho, Elisa Garcia; Urbinati, Elisabeth Criscuolo [UNESP] (Hindawi, 2004)
The dynamics of plasma cortisol, blood glucose, plasma chloride and liver glycogen were investigated in matrinxã (Brycon cephalus) submitted to capture and various periods of crowding. A total of 400 fish (700 ± 22 g weight) were distributed in four ponds divided into four 50-m2 squares (25 fish/square, 350 gL-1), where they were acclimated for 30 days. On the sampling day, after 24 h without food, all fish from three squares were transferred to the fourth square. Six fish were sampled before the procedure (control group, zero time) and 1, 3, 6 and 24 h after the capture and crowding. Each sampling was performed in a different pond to prevent additional stress. Fish were anaesthetized and blood and liver collected for biochemical analysis. Water temperature, pH, dissolved oxygen, alkalinity, ammonia and nitrite levels were within acceptable levels for matrinxã rearing. Slight but not significant increases were verified in plasma cortisol and blood glucose levels, as were decreases in plasma chloride and liver glycogen levels. The results suggest that matrinxã is highly tolerant to the procedures of capture and short-term crowding.
Keywords: Capture; Cortisol; Crowding; Glucose; Matrinxã; Stress; fish culture; handling stress; physiological response; stocking density; Brycon; Brycon cephalus; Vertebrata